Evidence for central antispastic effect of botulinum toxin type A. (6th November 2019) - Matak, Ivica
Abstract : Background and Purpose: Botulinum toxin type A (BoNT/A) injections into hyperactive muscles provide effective treatment for spasticity and dystonias, presumably due to its local effects on extrafusal and intrafusal motor fibres. A recent discovery of toxin's retrograde axonal transport to CNS might suggest additional action sites. However, in comparison to cholinergic peripheral terminals, functional consequences of BoNT/A direct central action on abnormally increased muscle tone are presently unknown. To address this question, the central effects of BoNT/A were assessed in experimental local spastic paralysis. Experimental Approach: Local spastic paralysis was induced by injection of tetanus toxin (1.5 ng) into rat gastrocnemius. Subsequently, BoNT/A (5 U·kg −1 ) was applied i.m. into the spastic muscle or intraneurally (i.n.) into the sciatic nerve to mimic the action of axonally transported toxin. Functional role of BoNT/A transcytosis in spinal cord was evaluated by lumbar i.t. application of BoNT/A‐neutralizing antitoxin. BoNT/A effects were studied by behavioural motor assessment and cleaved synaptosomal‐associated protein 25 (SNAP‐25) immunohistochemistry. Key Results: Tetanus toxin evoked muscular spasm (sustained rigid hind paw extension and resistance to passive ankle flexion). Subsequent injections of BoNT/A, i.m. or i.n, reduced tetanus toxin‐evoked spastic paralysis. Beneficial effects of i.n. BoNT/A and occurrence of cleaved SNAP‐25 in ventral horn were prevented by i.t. antitoxin. Conclusions and Implications: Axonally transported BoNT/A relieves muscle hypertonia induced by tetanus toxin, following the trans‐synaptic movement of BoNT/A in the CNS. These results suggest that such direct, centrally mediated reduction of abnormal muscle tone might contribute to the effectiveness of BoNT/A in spasticity and hyperkinetic movement disorders.